Isolate and diagnose fungi contaminated seeds, nuts traded in local markets in the city off Al-Diwaniya - A.K.Ziadi, Saba (Al-Qadisiyah Journal of Pure Science, 2018)
This study amied to identify fungi that infect the seed nuts traded in local markets in the city of Diwaniyah and intended for human consumption , namely, ( walnuts, almonds, Cashew , Pistachio, and seeds of the mixed of nuts Castania ) as it has been to isolate and diagnose 8 kinds innate is (P.italicum, A.ocherous, A.niger, R.stolanifer , F.Solani, C.lunata T.harizanum), in addition to yeast (G. candida)on 5 circles agricultural is (Yeast extract agar, Malt extract agar, Potato Dextrose agar, Sabroud Dextrose agar, Simmon citrate agar) The results indicate the existence of significant differences in the proportion of presence fungi below probability of P <0.05, as the results showed the highest pollution fungi are the seeds of pistachios, followed by seed nut and was the highest frequency of the fungus P.italicum on the middle food PDA as the percentage of impressions ( 61.53 %) for seed nut ( 57.14 %) on the middle food (Yeast ea) the seeds of peanuts , but for the seeds of almonds log fungus R. stolanifer percentage frequency ( 100.00% ) on the middle (PDA) and mushrooms P. italicum percentage frequency ( % 72.72 ) on the middle (Malt ea) As for the seeds of the problem of the brand ( Castaa ) scored fungus T.harizanum the emergence ratio ( 100.00%) on AGRO circles ( SDA ) and (Malt ea) and record the appearance of G. candida yeast ( 100.00 % ) on the middle pea